Torted and Ruptured Wandering Spleen Presenting as a Surgical Emergency in Pregnancy - A. Parvaiz; S. Chandran; A. Karim; K. Kumar; P. Jeffrey; N.R.F. Lagattolla (The Scientific World Journal)
Wandering spleen (WS) is characterised by incomplete fixation of the spleen to its supporting linorenal and gastrosplenic ligaments. It can predispose to life-threatening complications due to torsion of its vascular pedicle, splenic infarction, portal hypertension, and haemorrhage. A 27-year-old, 36-week prima gravida underwent emergency caesarean section for tachycardia and hypotension. A healthy baby girl was delivered. However, she remained shocked despite aggressive fluid therapy and intraoperatively it was noted that there was significant intraperitoneal bleeding and the on-call surgical team was summoned. Midline laparotomy revealed a lacerated, infarcted, hypermobile spleen found with free intraperitoneal bleeding. The unsalvageable spleen was resected and the patient went on to make an excellent recovery. The aetiology of WS is contentious. With an increased frequency among multiparous females of reproductive age, some suggest the hormonal effects of pregnancy as contributing factors. Clinical presentations range from an asymptomatic abdominal mass to acute abdominal pain with hypovolaemic shock. WS poses a serious threat to life due to thrombosis, bleeding, or infarction. Ultrasound scan and CT scan are equally effective in the diagnosis. Patients with asymptomatic WS should be treated with elective splenopexy, however, in the acute presentation, splenectomy is the procedure of choice.